Influence of sustainable practices in management accounting and decision-making : An industry comparative study - Sarmaja, Simon (My University, 2025)
Over the past few decades, sustainability and sustainable practices have garnered significant attention in both public discourse and the business environment. It has been integrated as a central element of corporate governance, driven by increasing regulatory requirements, stakeholder expectations, and global efforts to align business practices with environmental and social objectives. Organizations have primarily relied on existing regulatory and voluntary reporting frameworks, which have been sufficient to ensure compliance and maintain a positive public image of their actions. As concerns about sustainability grow, demand for transparency and comparability is expected to increase. Once considered sufficient for monitoring financial and non financial information, companies are now required to disclose the broader impact of organizations’ environmental and social activities. Starting in 2025, the Corporate Sustainability Reporting Directive (CSRD) requires European companies to report on their sustainability practices in accordance with the newly established European Sustainability Reporting Standards (ESRS). This reflects a significant paradigm shift in the regulatory and sustainability reporting environment. This development challenges traditional financial focused management accounting (MA) models and compels organizations to integrate environmental, social, and governance (ESG) data into their management control and decision making systems. This thesis examines the impact of sustainable practices and decision making objectives across three key industries: energy, food, and finance. While prior research has mainly focused on the external dimensions and effects of sustainability, such as investor communication and brand image, this thesis examines the effects in MA and internal processes. The guiding framework of this study is built on stakeholder theory, institutional theory, and legitimacy theory, which support the understanding of how expectations, societal norms, and regulatory forces reshape an organization's internal practices. Previous literature has identified different challenges in comparability, relevance, and usability of sustainability data. These limitations have raised questions about the role of management accountants (MAs) and the effectiveness of existing management tools in supporting sustainability driven strategies and decisions. The study employs a qualitative comparative methodology to deepen the understanding of these different dynamics. Semi structured interviews are conducted with accounting, finance, and sustainability professionals from Finnish companies. The data is transcribed and analysed to discover the key differences and similarities across sectors. The empirical findings indicate that while sustainability practices are increasingly shaping management control, due to rising information needs and shifting responsibilities, their direct impact on MA functions remains limited. Across all the interviewed sectors, sustainability and sustainability reporting initiatives are primarily led by specific ESG teams and professionals. The clear role separation has led to a situation where accountants have had minimal or no involvement. This segmentation can be partly explained by limited resources and a lack of sustainability expertise among accounting professionals. Despite possessing analytical skills, MAs appear to only continue having a support role, while sustainability experts manage complex ESG requirements. What is clear is that sustainability is becoming an increasingly important element in corporate strategy and decision making processes across all sectors. In the finance sector, it enhances risk management by integrating environmental and social dimensions into financial analyses. In the food and beverage industry, sustainability provides not only a means to address environmental challenges but also to meet market demands. Furthermore, the findings indicate that sustainability is not only viewed as an ethical choice or a means to enhance brand image, but also as a strategic necessity that redefines value beyond an economic perspective.

Viime vuosikymmeninä vastuullisuus ja vastuulliset käytännöt merkittävää huomiota sekä julkisessa keskustelussa että liiketoimintaympäristössä. Siitä on tullut keskeinen osa yritysjohtamista lisääntyvien sääntelyvaatimusten, sidosryhmien odotusten ja globaalien pyrkimysten vauhdittamana yhdenmukaistaa liiketoimintakäytännöt ympäristö ja sosiaalisten tavoitteiden kanssa. Organisaatiot ovat pääasiassa luottaneet olemassa oleviin sääntely ja vapaaehtoisiin raportointikehyksiin, jotka ovat riittäneet varmistamaan vaatimustenmukaisuuden ja ylläpitämään myönteistä julkista kuvaa toiminnastaan. vastuullisuutta koskevien huolenaiheiden kasvaessa läpinäkyvyyden ja vertailukelpoisuuden kysynnän odotetaan kasvavan. Aiemmin taloudellisten ja muiden kuin taloudellisten tietojen seurantaan riittävinä pidettyjen tietojen avulla yritysten on nyt julkistettava organisaatioiden toiminnan laajempi vaikutus ympäristöön ja sosiaalisiin tekijöihin. Vuodesta 2025 alkaen yritysten vastuullisuusraportointia koskeva direktiivi (CSRD) edellyttää eurooppalaisilta yrityksiltä raportoivan vastuullisista käytännöistään uusien raportointistandardien (ESRS) mukaisesti. Tämä heijastaa merkittävää paradigman muutosta sääntely ja vastuullisuuden raportointiympäristössä. Se haastaa perinteiset talouspainotteiset johdon laskentatoimen (MA) mallit ja pakottaa organisaatiot integroimaan ESG:hen liittyvät tiedot johdon valvonta ja päätöksentekojärjestelmiinsä. Tämä opinnäytetyö tarkastelee vastuullisia käytäntöjä ja päätöksentekoa kolmella keskeisellä toimialalla: energia, elintarvike ja rahoitusalalla. Aiempi tutkimus on keskittynyt pääasiassa vastuullisuuden ulkoisiin ulottuvuuksiin ja vaikutuksiin, kuten sijoittajaviestintään ja brändikuvaan, kun taas tämä opinnäytetyö tarkastelee vaikutuksia johdon laskentatoimeen ja organisaation sisäisiin prosesseihin. Tutkimuksen ohjaava viitekehys perustuu sidosryhmä, institutionaali, ja legitimiteettiteoriaan, jotka tukevat ymmärrystä siitä, miten odotukset, yhteiskunnalliset normit ja sääntelyt muokkaavat organisaation sisäisiä käytäntöjä. Aiempi kirjallisuus on tunnistanut erilaisia haasteita vastuullisuustietojen vertailukelpoisuudessa, relevanssissa ja käytettävyydessä. Nämä rajoitukset herättävät kysymyksiä johdon kirjanpitäjien roolista ja olemassa olevien johtamistyökalujen tehokkuudesta vastuullisten strategioiden ja päätösten tukemisessa. Tutkielmassa käytetään laadullista ja vertailevaa tutkimusotetta ymmärtääkseen erilaisia dynamiikkoja. Haastattelut toteutetaan puolistrukturoituna, ja niiden kohteena on suomalaisten yritysten kirjanpidon, rahoituksen ja vastuullisuus ammattilaiset. Haastattelutulokset litteroidaan ja analysoidaan keskeisten erojen ja yhtäläisyyksien löytämiseksi eri toimialojen välillä. Empiiriset tulokset osoittavat, että vaikka vastuulliset käytännöt voivat muokata sisäisen laskentatoimen roolia kasvavien tiedontarpeiden ja vastuiden siirtymisen vuoksi, niiden suora vaikutus johdon toimintoihin on edelleen rajallinen. Kaikilla haastatelluilla sektoreilla vastuullisuuden ja kestävän kehityksen raportointialoitteita johtavat ensisijaisesti erilliset ESG tiimit ja ammattilaiset. Selkeä roolien jako on johtanut tilanteeseen, jossa kirjanpitäjät ovat osallistuneet vain vähäsen tai ei lainkaan. Tätä voidaan osittain selittää resurssien ja laskentatoimen ammattilaisten osaamisen puutteella. Analyyttisistä taidoista huolimatta kirjanpitäjillä näyttää olevan vain tukeva rooli, kun taas vastuullisuusasiantuntijat hallinnoivat monimutkaisia ESG vaatimuksia. Vastuullisuudesta on kuitenkin tulossa yhä tärkeämpi tekijä strategian kehittämisessä ja päätöksentekoprosesseissa kaikilla sektoreilla. Rahoitusalalla se parantaa riskienhallintaa integroimalla ympäristö ja sosiaaliset tekijät taloudellisiin analyyseihin. Elintarvike ja juomateollisuudessa vastuullisuus tarjoaa keinon vastata niin ympäristöhaasteisiin kuin markkinavaatimuksiin. Lisäksi tulokset osoittavat, että vastuullisuutta ei pidetä ainoastaan eettisenä valintana tai keinona parantaa brändikuvaa, mutta myös strategisena välttämättömyytenä, joka laajentaa arvon tarkastelua taloudellisten mittarien ulkopuolelle.
Keywords: Sustainability reporting, sustainability, CSRD, management accounting, decision-making, vastuullisuusraportointi, vastuullisuus, CSRD, johdon laskentatoimi, päätöksenteko